Digital Slavery in Tiktok Social Media Christian Fuchs Perspective - Ibnu Azka (Ilomata International Journal of Social Science, 2023)
Initially, the practice of slavery was known as physical violence, this is commonplace in several countries that used to be very thick with the practice of slavery, this era actually transmits various new forms of exploitation, especially through digital media. This article discusses the practice of digital slavery on social media TikTok. The large number of begging practices on social media TikTok indicates an act of exploitation unnoticed by those who do it, this can be referred to as the practice of slavery.This research uses a netnography qualitative descriptive method by tracing and analyzing accounts that often live stream on TikTok by selling themselves. This article wants to answer some of the following questions. First, what is Christian Fuchs' view of the practice of slavery? Second, how is the model of digital slavery on social media TikTok. The results of this study show First, that Fuchs views digital media as having shaped the exploitation and commodification of social media, social media often utilizes data and content generated by users as a source of economic value. In this context, social media users are often unpaid "laborers", as they indirectly contribute to creating value for the platform, but rarely get the equivalent in return. Implications: Slavery is not only through physical touch, but through digital technology.